Consumer behavior in wine tourism contexts: the case of La Rioja, Spain - Meraz Ruiz, Lino (2025)
This study analyzes the factors that influence wine consumer behavior in La Rioja, Spain, focusing on perception, disposition, and the influence of reference groups and wineries’ branding strategies. The research was based on 300 structured interviews with visitors to Bodegas Franco Españolas, highlighting the demographic and educational profile of the participants. The acceptance of a Tempranillo wine was assessed using a Likert- scale questionnaire and structural equation modeling with partial least squares was applied to analyze the variables related to purchase intention and positive emotions. The results showed significant relationships and a well-adjusted model, statistically validated with confidentiality tests, convergent and discriminant validity, and absence of multicollinearity. This work contributes to understanding consumer behavior in a key wine-producing region, providing input for marketing and tourism development strategies.